Identification of the molecular determinants of antagonist potency in the allosteric binding pocket of human P2X4 - Pasqualetto, Gaia; Zuanon, Marika; Brancale, Andrea; Young, Mark T. (Frontiers in Pharmacology, 2023)
P2X receptors are a family of ATP-gated cation channels comprising seven subtypes in mammals, which play key roles in nerve transmission, pain sensation and inflammation. The P2X4 receptor in particular has attracted significant interest from pharmaceutical companies due to its physiological roles in neuropathic pain and modulation of vascular tone. A number of potent small-molecule P2X4 receptor antagonists have been developed, including the allosteric P2X4 receptor antagonist BX430, which is approximately 30-fold more potent at human P2X4 compared with the rat isoform. A single amino-acid difference between human and rat P2X4 (I312T), located in an allosteric pocket, has previously been identified as critical for BX430 sensitivity, implying that BX430 binds in this pocket (Ase et al., 2019). Using a combination of mutagenesis, functional assay in mammalian cells and in silico docking we confirmed these findings. Induced-fit docking, permitting the sidechains of the amino-acids of P2X4 to move, showed that BX430 could access a deeper portion of the allosteric pocket, and that the sidechain of Lys-298 was important for shaping the cavity. We then performed blind docking of 12 additional P2X4 antagonists into the receptor extracellular domain, finding that many of these compounds favored the same pocket as BX430 from their calculated binding energies. Induced-fit docking of these compounds in the allosteric pocket enabled us to show that antagonists with high potency (IC50 ≤ 100 nM) bind deep in the allosteric pocket, disrupting a network of interacting amino acids including Asp-85, Ala-87, Asp-88 and Ala-297, which are vital for transmitting the conformational change following ATP binding to channel gating. Our work confirms the importance of Ile-312 for BX430 sensitivity, demonstrates that the allosteric pocket where BX430 binds is a plausible binding pocket for a series of P2X4 antagonists, and suggests a mode of action for these allosteric antagonists involving disruption of a key structural motif required for the conformational change induced in P2X4 when ATP binds.